Mother's Efforts in Increasing Breast Milk Production - Gadhis Yunita Sari; Yuni Puji Widiastuti; Istioningsih Istioningsih; Sri Rejeki (Global Health Science Group, 2020)
Exclusive breastfeeding coverage in Indonesia is only 42%. The low number of breast milk covers is due to the smooth production of breast milk. The smooth production of breast milk can be increased by various efforts, including maternal efforts. This research aims is to assess mothers' efforts to increase breast milk production. This research design is descriptif with crossectional design. The number of responden are 57 responden with total sampling. The results of this study represent the majority of mothers' efforts to increase breast milk production in the